Reallocation of Cyamiocardium crassilabrum Dell, 1964, into Perrierina Bernard, 1897 (Bivalvia, Cyamiidae) - Zelaya, Diego Gabriel (2008)
Re-examination of the holotype of Cyamiocardium crassilabrum Dell, 1964, allowed confirmation that the species was wrongly allocated to the genus Cyamiocardium. This material, together with additional specimens from the western Malvinas (Falklands) Islands allowed for a re-description of that species. The species is also properly illustrated through scanning electron microscopy, and its updated generic placement discussed. The presence of a “taxodont” hinge plate is the main morphological character supporting the re-allocation of this species in the genus Perrierina Bernard, 1897. Information on the brooding condition of the species is provided.